Family structure and childhood anthropometry in Saint Paul, Minnesota in 1918. Issue 2 (3rd July 2017) - Roberts, Evan; Warren, John Robert
Abstract: Concern with childhood nutrition prompted numerous surveys of children's growth in the United States after 1870. The Children's Bureau's 1918 'Weighing and Measuring Test' measured two million children to produce the first official American growth norms. Individual data for 14, 000 children survives from the Saint Paul, Minnesota survey whose stature closely approximated national norms. As well as anthropometric details the survey recorded exact age, street address and full name. These variables allow linkage to the 1920 census to obtain demographic and socio-economic information. We matched 72% of children to census families creating a sample of nearly 10, 000 children. Children in the entire survey (linked set) averaged 0.74 (0.72) standard deviations below modern World Health Organization height-for-age standards, and 0.48 (0.46) standard deviations below modern weight-for-age norms. Sibship size strongly influenced height-for-age, and had weaker influence on weight-for-age. Each additional child aged six or under reduced height-for-age scores by 0.07 standard deviations (95% confidence interval: –0.03, 0.11). Teenage siblings had little effect on height-for-age. Social class effects were substantial. Children of laborers averaged half a standard deviation shorter than children of professionals. Family structure and socio-economic status had compounding impacts on children's stature.